The role of TGF-β superfamily in endometriosis: a systematic review - Xu, Xinyi; Li, Jun; Lin, He; Lin, Zhe; Ji, Guangcheng (Frontiers in Immunology, 2025)
IntroductionEndometriosis is a prevalent chronic gynecological disorder. Globally, endometriosis affects approximately 5–10% of women of reproductive age, leading to symptoms such as dysmenorrhea, chronic pelvic pain, and infertility. While the precise etiology of endometriosis remains unclear, various etiological theories have been suggested to explain the condition’s development. Recent research has focused on the TGF-β superfamily, which regulates cell proliferation, differentiation, migration, and immune modulation, and is increasingly recognized as a key contributor to the pathogenesis of endometriosis.MethodsThis review provides a comprehensive examination of TGF-β superfamily in endometriotic lesions. According to the recommendations of the Preferred Reporting Project for Systematic Review and Meta-Analysis (PRISMA) guidelines, a literature search was conducted in the PubMed and Web of Science database until April 30, 2025.ResultsTGF-β superfamily contributes not only to the adhesion, invasion, and proliferation of ectopic endometrial cells but also to the mediation of fibrosis, immune modulation, and angiogenesis within endometriotic lesions. Considering the parallels between endometriosis and malignant processes, including local invasion and abnormal tissue growth, analyzing the TGF-β-mediated mechanisms offers new insights into disease progression and its oncological parallels. Exploration of TGF-β-dependent biomarkers and targeted inhibitors holds potential in advancing more effective diagnostic and therapeutic approaches.DiscussionThis study emphasizes further research into TGF-β and related pathways, potentially paving the way for innovative, targeted therapeutic strategies aimed at managing endometriosis, reducing recurrence rates, and enhancing the quality of life for affected women.